Efektifitas Metode Dicovery Learning Dalam Meningkatkan Hasil Belajar Bahasa Inggris Siswa: Eksperimen di Kelas X SMAIT Asy-Syukriyyah Tangerang - Aris Setyawan (STAI Asy-Syukriyyah, 2019)
The aim of this research is to know student English learning outcomes using Discovery Learning learning methods and to find out student learning activities in English learning. The population of this research is all grade X students of SMA Asy-Syukriyyah. The research sample was taken by random sampling technique. This research was started with a pretest and then was treated using the Discovery Learning learning method. Based on the results of testing the research hypothesis and analysis of data processing found that Sig. (2-tailed) is 0,000 where 0,000 <0.05. So H0 is accepted and Ha is rejected. Thus there is a difference between the value of learning outcomes before the discovery learning method is treated with the learning outcomes have been carried out treatment using the discovery learning method. Thus, It can be concluded that the method of discovery learning is very effective in improving the English learning outcomes of students of class X in SMA Asy-Syukriyyah.